KEDUDUKAN DAN TANGGUNG JAWAB PERUSAHAAN MULTINASIONAL (MNC) DALAM HUKUM INTERNASIONAL - Sitha Rambisa, Lila; Suksma Prijandhini Devi Salain, Ni Made (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013)
Free Trade Agreements attract many Multi National Corporations (MNCs) to invest in other countries. The economic impact of MNCs, made some difficulties to developing countries in enforcing national laws. This condition brings international law to try to fill the gap when the national law failed to make MNCs to responsible for damage caused by activities of the company. But the fact that MNCs do not have legal personality under international law has become the main obstacle in the implementation of international law This paper is intended to discuss the MNC status under international law, and analysis how efforts of International Law in the imposition of liability for Multi National Corporations.
Keywords: Multi-National Corporations, Legal Personality, Responsibility